DAMPAK PENGGUNAAN MESIN PANEN (COMBINE HARVESTER) TERHADAP EFISIENSI DAN EFEKTIVITAS USAHA TANI PADI SAWAH DI KECAMATAN SAMPANG KABUPATEN SAMPANG: PENGGUNAAN MESIN PANEN (COMBINE HARVESTER) TERHADAP EFISIENSI DAN EFEKTIVITAS USAHA TANI PADI SAWAH DI KECAMATAN SAMPANG KABUPATEN SAMPANG - Dewi Fatimah; Eko Murniyanto; Tety Sugiarti (Innofarm:Jurnal Inovasi Pertanian, 2023)
This study aims (1) to analyze the impact of using combine harvesters on rice farming income in paddy fields (2) analyzing the effectiveness of using combine harvesters for natural resources in rice farming in paddy fields.This survey research method was conducted by interviewing a number of respondents calculated by the Slovin equation. The data were analyzed by descriptive quantitative.The results showed that (1) the income of lowland rice farming using the combine harvester yielded higher grain production compared to not using the sickle, thresher and manual container harvesting equipment, (2) the effectiveness of using the combine harvester harvesting equipment, namely lower harvest costs, time faster, less labor required at harvest but damage to bunds can cause problems if harvesting is not simultaneous in one area.